Psychosynteza. Całościowa koncepcja osobowości człowieka = Psychosynthesis - holistic conception of human being - Białek, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
Conseived by the ltalian psychiatrist, founder of psychosynthesis, Roberto Assagioli (1888-1974), "psychosynthesis" is a unified conception of human development and an organised system of techniques which can be applied in the fields of therapy, education and medicine. Psychosynthesis provides the broadest understanding of what is meant by the whole person including our physical, mental, emotional and spiritual dimensions, and it extends and synthesizes this concept of the individual with the larger whole: inter-individual relationships with others and Nature.
Keywords: psychosynteza